Preparation, Structural Characterization, and Hypoglycemic Activity of Dietary Fiber from Sea Buckthorn Pomace - Qi Xiao; Liting Yang; Jingjing Guo; Xiyu Zhang; Yu Huang; Qun Fu (Foods)
Sea buckthorn pomace is often discarded as a by-product during the sea buckthorn processing stage. Consequently, its richness in dietary fiber is usually overlooked. In this study, soluble dietary fiber (SDF) and insoluble dietary fiber (IDF) were extracted from sea buckthorn pomace using ultrasound combined with the enzyme method. The optimal values of the independent variable were determined by a combinatorial design and a response surface optimization test with SDF/IDF as the dependent variable, prepared as follows: 5% enzyme addition, ultrasonic power of 380 W, enzymatic time of 30 min, and alcoholic precipitation liquid ratio of 4:1. Under these conditions, the SDF/IDF ratio was 17.07%. The structural characterization and hypoglycemic activity of the two dietary fibers were then compared. The results show that two dietary fibers have respective structures and functional groups of fibers. SDF was less crystalline than IDF, and its structure was looser. Furthermore, the hypoglycemic activity of SDF was significantly better than IDF’s (p < 0.05). The glucose adsorption capacity of SDF was 1.08–1.12 times higher than that of IDF. SDF inhibited α-amylase and α-glucosidase by 1.76 and 4.71 times more than IDF, respectively. These findings provide a reference for improving the utilization of sea buckthorn processing by-products.